HABITUATION TO SIGNING CHILDREN'S SONGS TO EMBED CHARACTER VALUES IN LOW GRADE STUDENTS OF SDN 1 DEPOKREJO - Heni Rahmawati; Anjar Wijiatmiko; Novia Indrianingsih; Rokhmaniyah Rokhmaniyah (Universitas Sebelas Maret, 2018)
Children's songs contain many character values. So that the character values contained in these songs can be measured in the souls of children, it is necessary to spread the habit of singing children's songs. Research activities need to be carried out in order to find out ways and activities of habituation to sing children's songs in instilling character values. The approach taken in this study is qualitative research with low-grade students at Depokrejo 1 Elementary School. Primary data sources are obtained by interviewing teachers and direct observation. To maintain the validity of the data, this study uses a triangulation method. The results showed that the habit of singing children's songs to low-grade students at Depokrejo 1 Elementary School was successful and could make students better than before, for example more fellow friends, forgiveness, courtesy, maintaining cleanliness, and so on.